MiR‐10a‐5p is increased in atopic dermatitis and has capacity to inhibit keratinocyte proliferation. Issue 11 (6th June 2019) - Vaher, Helen; Runnel, Toomas; Urgard, Egon; Aab, Alar; Carreras Badosa, Gemma; Maslovskaja, Julia; Abram, Kristi; Raam, Liisi; Kaldvee, Bret; Annilo, Tarmo; Tkaczyk, Eric R.; Maimets, Toivo; et al.
Abstract: Background: miR‐10a‐5p has been shown to regulate cancer cell proliferation and invasiveness and endothelial cell inflammatory responses. The function of miR‐10a‐5p in the skin has not been previously studied. The aim of the current study was to examine miR‐10a‐5p expression, regulation, and function in keratinocytes (KCs) in association with atopic dermatitis (AD). Methods: The expression of miR‐10a‐5p and its target genes was analyzed using RT‐qPCR, mRNA array analysis, in situ hybridization, and immunofluorescence. The transfection of miRNA mimics, cell cycle distribution analysis, and luciferase assays was used to study miR‐10a‐5p functions in human primary KCs. Results: miR‐10a‐5p was found to be upregulated in lesional skin from patients with AD and in proliferating KCs. Array and pathway analysis of IL‐1β‐stimulated KCs revealed that miR‐10a‐5p inhibited many genes that affect cell cycle progression and only a few inflammation‐related genes. Accordingly, fewer cells in S‐phase and reduced proliferation were detected as characteristics of miR‐10a‐5p‐transfected KCs. The influence of miR‐10a‐5p on cell proliferation was also evident in KCs induced by AD‐related cytokines, including IL‐4, IL‐17, and IL‐1β, as measured by the capacity to strongly suppress the expression of the proliferation marker Ki‐67. Among AD‐related putative direct target genes, we verified hyaluronan synthase 3, a damage‐associated positive regulator of KC migration and proliferation, as a direct target of miR‐10a‐5p. Conclusions: miR‐10a‐5p inhibits KC proliferation and directly targets hyaluronan synthase 3 and thereby may modulate AD‐associated processes in the skin. Abstract : The expression of miR‐10a‐5p is increased in the skin of patients with atopic dermatitis, in proliferating keratinocytes, and in response to growth factor heparin‐binding EGF‐like growth factor. miR‐10a‐5p has capacity to inhibit keratinocytes proliferation, the expression of mitogen‐activated kinase 3 kinase 7 and hyaluronan synthase 3, pro‐inflammatory chemokines IL‐8 and CCL5, and numerous genes affecting cell cycle progression. miR‐10a‐5p inhibits proliferation and to less extent the inflammation and cell adhesion of keratinocytes and thereby may affect the development and severity of atopic dermatitis.